Improved method of water removal from vegetable oil - Musil, Martin; Hájek, Martin; Skopal, František; Vávra, Aleš (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
This paper is about water removal from vegetable oil. Commonly, used drying methods are expensive. Oil dried for transesterification yields improvement and side reaction suppression. Water promotes an undesirable side reactionsaponification of oil. Drying was performed at different pressures and with various additions of alcohol as methanol, ethanol and butanol. The experiment shows that addition of just a small amount of alcohol during vacuum distillation decreased water content to 50ppm.
Zlepšení metody odstraňování vody z rostlinného oleje
Keywords: Vegetable oil; Alcohol; Water removal; Moisture; Azeotrope; rostlinný olej; alkohol; sušení; vlhkost; azeotrop